INTEGRASI NILAI QUR’AN-HADIS DALAM PENGEMBANGAN KURIKULUM LOGIKA DAN NUMERASI DI LEMBAGA PENDIDIKAN - M. Agus Maksum; Mufatihatut Taubah (Tadbir: Jurnal Manajemen Pendidikan Islam, 2026)
This study analyses the integration of Qur'an-Hadith values in the development of logic and numeracy curricula in Islamic educational institutions as an effort to build rational, analytical, and ethical thinking competencies. Using a qualitative approach and case study design, this study explores the theological basis of logical thinking abilities, the urgency of numeracy literacy in modern education, and curriculum strategies that combine spiritual values with cognitive skills. The results show that verses about tafakkur, tadabbur, and hisab can be the basis for strengthening systematic and numerical thinking structures. The implementation of integration in schools includes the formulation of integrative learning objectives, the development of thematic modules, and a values-based active learning approach. However, a number of challenges have emerged, such as teacher capacity, the availability of teaching materials, and the need for authentic evaluation instruments. This study emphasises that the integration of Qur'an-Hadith values is important for creating students who are academically competent and religious in character.